Enhancing nursing education to bolster nurse governance: insights from nurse managers - Choi, Sujin (Frontiers in Medicine, 2023)
Aim In South Korea, the level of nursing governance is moving toward shared governance. This study sought to explore nursing education contents in undergraduate nursing programs necessary to improve the governance of nurses from the perspectives of nurse managers. Methods The study employs thematic analysis following the guidelines outlined in the Consolidated Criteria for Reporting Qualitative Research utilizing a qualitative research design. Our investigation involves general or tertiary hospital nurse managers intending to gain valuable insights and perspectives. Results Interview data from 14 nurse managers were analyzed. A total of one main and four sub-themes were derived from the qualitative data analysis. Analysis revealed the main theme, “occupational socialization.” The four sub-themes were education on “nurse–patient and nurse-colleague communicative interaction,” “humanity,” “career development,” and “nurses as politicians.” Conclusion The findings are valuable in suggesting critically needed educational content in undergraduate nursing programs to improve nursing governance. Future research should investigate the effects of the abovementioned themes on nursing governance among clinical nurses or nursing students for several years of follow-up data collection.